2022
DOI: 10.3390/genes13050723
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation Mechanisms of the Cofilin-1 Gene in the Development and Differentiation of Bovine Primary Myoblasts

Abstract: As the quality of beef products has received increasing attention, it is essential to explore the underlying transcriptional and epigenetic mechanisms of meat traits. Our project uses Qinchuan cattle as the research subject. First, we examined the spatiotemporal expression pattern of the CFL1 gene in a panel of fetal bovine, calf, and adult cattle samples. Then, we performed DNA methylation experiments of CFL1 on myogenesis and muscle maturation using the BSP amplification and COBRA sequencing techniques and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recent evidence indicates that cofilin family genes ( CFL1 and CFL2 ) participate in actin cytoskeleton remodeling [ 40 ]. Notably, the CFL1 and CFL2 genes can be expressed simultaneously in embryonic skeletal muscle, whereas the CFL2 gene replaces the CFL1 gene in the late stage of differentiation [ 6 , 8 ]. This means that cofilin only presents one subtype ( CFL1 or CFL2 ) along with the muscle cell growth and development in healthy mouse [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence indicates that cofilin family genes ( CFL1 and CFL2 ) participate in actin cytoskeleton remodeling [ 40 ]. Notably, the CFL1 and CFL2 genes can be expressed simultaneously in embryonic skeletal muscle, whereas the CFL2 gene replaces the CFL1 gene in the late stage of differentiation [ 6 , 8 ]. This means that cofilin only presents one subtype ( CFL1 or CFL2 ) along with the muscle cell growth and development in healthy mouse [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary bovine myoblasts (PBMs) were harvested from fetal bovine longissimus dorsi muscle and cultured by collagenase-I digestion as previously described [ 13 ]. Cell lines and PBMs were cultured following our previously established protocols [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported DNA methylation in the muscle of fetal and adult Hu sheep, highlighting ADIPOQ (adiponectin, C1Q and collagen domain containing), CCNA2 (cyclin A2), ITGA2 (integrin subunit alpha 2), and MYOG (myogenin) as mediators of muscle growth and metabolism . Nevertheless, meat quality is a very complex trait, determined by multiple regulatory mechanisms, , such as epigenetic marks/factors, , miRNAs, translation regulation, RNA/peptide degradation, and post-translational modification . Therefore, the combined analysis of the transcriptome, small noncoding RNAs, and DNA methylation can provide a comprehensive understanding of the molecular mechanisms that determine meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…Both the CFL2 gene and CFL1-AS1 parent gene CFL1 are closely related to muscle growth and development and play an important role in normal muscle function and regeneration. Previous studies have shown that the CFL1 and CFL2 genes are specifically expressed in different growth and development stages of bovine muscle and show opposite expression patterns during muscle cell differentiation [ 17 , 18 ]. RNAhybrid analysis identified a miR-125b binding site on CFL1-AS1, and studies have shown that miR-125b can regulate the proliferation and differentiation of myoblasts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%